Rabbit hemorrhagic disease virus VP60 protein expressed in recombinant swinepox virus self-assembles into virus-like particles with strong immunogenicity in rabbits - Liu, Changjin; Lin, Min; Hu, Huanyi; Liu, Xiaolan; Bian, Yanchao; Huang, Xiaohua; Li, Xiaoxiang; Yu, Wenyang; Luo, Feng; Deng, Shunzhou (Frontiers in Microbiology, 2022)
Rabbit Hemorrhagic Disease (RHD) is an economically significant infectious disease of rabbits, and its infection causes severe losses in the meat and fur industry. RHD Virus (RHDV) is difficult to proliferate in cell lines in vitro, which has greatly impeded the progress of investigating its replication mechanism and production of inactivated virus vaccines. RHDV VP60 protein is a major antigen for developing RHD subunit vaccines. Herein, we constructed a TK-deactivated recombinant Swinepox virus (rSWPV) expressing VP60 protein and VP60 protein coupled with His-tag respectively, and the expression of foreign proteins was confirmed using immunofluorescence assay and western blotting. Transmission electron microscopy showed that the recombinant VP60, with or without His-tag, self-assembled into virus-like particles (VLPs). Its efficacy was evaluated by comparison with available commercial vaccines in rabbits. ELISA and HI titer assays showed that high levels of neutralizing antibodies were induced at the first week after immunization with the recombinant strain and were maintained during the ongoing monitoring for the following 13 weeks. Challenge experiments showed that a single immunization with 106 PFU of the recombinant strain protected rabbits from lethal RHDV infection, and no histopathological changes or antigenic staining was found in the vaccine and rSWPV groups. These results suggest that rSWPV expressing RHDV VP60 could be an efficient candidate vaccine against RHDV in rabbits.